1994
DOI: 10.1200/jco.1994.12.5.986
|View full text |Cite
|
Sign up to set email alerts
|

Clinical activity of chronic oral etoposide in previously treated metastatic breast cancer.

Abstract: Chronic oral etoposide appears to be an active and well-tolerated regimen in MBC patients previously exposed to chemotherapy. This schedule of etoposide administration warrants further studies, alone or in combination, in MBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…Although doxorubicin has been most widely used, there is evidence of the efficacy of these agents in the treatment of breast cancer (26,27). Additionally, with recent reports of the expression of HER2 in other malignancies including gastrointestinal cancer, it is important to understand the interaction of trastuzumab with a variety of chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Although doxorubicin has been most widely used, there is evidence of the efficacy of these agents in the treatment of breast cancer (26,27). Additionally, with recent reports of the expression of HER2 in other malignancies including gastrointestinal cancer, it is important to understand the interaction of trastuzumab with a variety of chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Included studies were published between 1993 and 2015 and reported on a total of 483 patients ( Table 2). All studies except one that was retrospective (7), had a prospective phase II, non-randomized, one arm design (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Besides two studies that were from China (17,18), all other reports originated from Europe and the United States ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In the third study that included only patients receiving etoposide as a second or later line treatment, RR were 28.6% (four of 14 patients) in the second line, 35.8% (19 of 53 patients) in the third line, and 54.2% in the fourth or later line (15). Three studies reported on responses in different metastatic sites (11,12,15) and noticed that a variety of metastatic sites were among the responding sites. Another study performed a PFS analysis according to metastatic site and reported that patients with visceral metastases had a worse PFS than the rest of the populations in the study (18).…”
mentioning
confidence: 99%
“…Following the emergence of oral etoposide, the role of prolonged oral etoposide in the treatment of breast cancer was investigated in five phase II trials (Calvert et al, 1993;Martin et al, 1994;Palombo et al, 1994;Atienza et al, 1995;Bontenbal et al, 1995). Unlike the results of single agent i.v.…”
Section: Discussionmentioning
confidence: 99%